Hi

I want check my answer please >

look on Attachments

Printable View

- Dec 7th 2009, 04:41 AMr-soyI want check my answer please >
Hi

I want check my answer please >

look on Attachments - Dec 7th 2009, 08:07 AMkjchauhan
L.H.S.

$\displaystyle =\frac{\cos^2 z-3\cos z+2}{\sin^2 z}$

$\displaystyle =\frac{(1-\cos z)(2-\cos z)}{(1-\cos^2 z)}$

$\displaystyle =\frac{(1-\cos z)(2-\cos z)}{(1-\cos z)(1+\cos z)}$

$\displaystyle =\frac{(2-\cos z)}{(1+\cos z)}$

=R.H.S. - Dec 7th 2009, 11:17 AMr-soy
thanks , but can explain this steps specially the first one

- Dec 8th 2009, 02:02 AMmr fantastic